3=x+x+x.

Simple and best practice solution for 3=x+x+x. equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3=x+x+x. equation:



3=x+x+x.
We move all terms to the left:
3-(x+x+x.)=0
We add all the numbers together, and all the variables
-(+2x+x.)+3=0
We get rid of parentheses
-2x-x.+3=0
We move all terms containing x to the left, all other terms to the right
-2x-x.=-3

See similar equations:

| 165=4x+x^2 | | 6x+(28x÷2)-5x=15 | | 6n2=-12n-1 | | 11=y/6 | | -37-x=-8x-2(x+5) | | (5x-47)+(4x+2)=90 | | -2(x-3)-20=14 | | 84.8/n=10.6 | | 8(w+2)=50 | | 19-a=-7(4a+5) | | 15/6=n+7/9 | | -3(6x-9)+3=-18x+30 | | 4(x-5)=x-7 | | -9.2-3.2=4.7y-3.7y+6.1 | | 175m-100m+53,625=55,825-200m | | (2y-8)+27=3 | | 5x^2+108x=0 | | -5=7=(x+1)-3(x+8) | | -(7x-6)+4x=-2(x+2) | | (3x-4)+(4x+3)=90 | | 3(2x-1)=4x+2(x-8) | | 3x-13=2(x+13) | | 6x^2+15=63 | | -3(1+8x)+8(1-x)=69 | | -(7x-6)4x=-2(x+2) | | -7(x-5)=21 | | y/5-3=17 | | (3y-7)+3y=9 | | 5(4w+5)/2=8 | | 4(2+r)=12 | | 2×-4÷5=x+4 | | 3(m-6)-8(5-3m)=77 |

Equations solver categories